Iliopsoas tears in professional tennis: case reports in five cases - Parier, J.; Montalvan, B.; Bellaiche, L.; Brasseur, J. L. (Medicine and Science in Tennis, 2008)
Occasionally among professional tennis players in France, a tear of the musculo-tendinous junction of the iliopsoas muscle is observed. This report focuses on five encountered cases in a three year period. The pathology, imaging, natural history and treatment are discussed in the following article.